PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR DAN KEAKTIFAN MAHASISWA PGSD UNWIDHA - ani, fembri (LPPM Undiksha, 2017)
The research purposes to analyze: (1) improvement of student result of PGSD Unwidha and (2) student activeness to implementation of problem based learning. This research is conducted with 2 cycles. The subjects are PGSD students of Widya Dharma University Class B, force 2016 which take the basic science concept. There are 27 students. Student outcomes based on the evaluation after learning, while data implementation of problem based learning by lecturers obtained from the observation sheet of student activeness. Data analyzed on descriptively qualitative and quantitative. The results showed that (i) student outcomes increased with the success rate of 90% and (ii) students activeness achieve the optimal 77,7% categories very well. It shows that there is the increased from phase I to phase cycle II. The conclusion of this research is problem based learning model can improve learning outcomes and student activeness of PGSD Universitas Widya Dharma Klaten.